Population Trends, Bend Use Relative to Available Habitat and Within‐River‐Bend Habitat Use of Eight Indicator Species of Missouri and Lower Kansas River Benthic Fishes: 15 Years After Baseline Assessment. (4th November 2014) - Wildhaber, M. L.; Yang, W.‐H.; Arab, A.
Abstract: A baseline assessment of the Missouri River fish community and species‐specific habitat use patterns conducted from 1996 to 1998 provided the first comprehensive analysis of Missouri River benthic fish population trends and habitat use in the Missouri and Lower Yellowstone rivers, exclusive of reservoirs, and provided the foundation for the present Pallid Sturgeon Population Assessment Program (PSPAP). Data used in such studies are frequently zero inflated. To address this issue, the zero‐inflated Poisson (ZIP) model was applied. This follow‐up study is based on PSPAP data collected up to 15 years later along with new understanding of how habitat characteristics among and within bends affect habitat use of fish species targeted by PSPAP, including pallid sturgeon. This work demonstrated that a large‐scale, large‐river, PSPAP‐type monitoring program can be an effective tool for assessing population trends and habitat usage of large‐river fish species. Using multiple gears, PSPAP was effective in monitoring shovelnose and pallid sturgeons, sicklefin, shoal and sturgeon chubs, sand shiner, blue sucker and sauger. For all species, the relationship between environmental variables and relative abundance differed, somewhat, among river segments suggesting the importance of the overall conditions of Upper and Middle Missouri River and Lower Missouri and Kansas rivers on the habitat usage patterns exhibited. Shoal and sicklefin chubs exhibited many similar habitat usage patterns; blue sucker and shovelnose sturgeon also shared similar responses. For pallid sturgeon, the primary focus of PSPAP, relative abundance tended to increase in Upper and Middle Missouri River paralleling stocking efforts, whereas no evidence of an increasing relative abundance was found in the Lower Missouri River despite stocking. Copyright © 2014 John Wiley & Sons, Ltd.